Customer involvement through social media: the cases of some telecommunication firms - Valentina Della Corte; Alessandra Iavazzi; Chiara D'Andrea (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
This study highlights the contribution of the role of social media in supporting customer involvement for service innovation. It is commonplace that many service firms and processes have characteristics that differ from manufacturing. Analyzing the literature, we note that there are many contributions on innovation in the manufacturing industry while few researches are concentrated on the service industry. Hence, we chose to deepen the analysis on marketing innovation, with specific reference to the involvement of the customer, through social media, in service firms. One of the key aspects of many service activities is the high involvement of the client/customer/user in the production of the final service. Without this coproduction process (i.e. interactivity of service production), the service would have often not been created. This customer involvement, together with the intangibility of many service products, leads service innovation to assume characteristics that are different from those learned by studies on manufacturing innovation. Service innovation is hard to capture in traditional categories like product or process innovation: the coproduction process and the interactions between the service provider and his client originate from so many touch points that it becomes difficult to identify what is the focus of innovation in service firms. Hence, the focus is on the role of innovation in marketing activities in favoring the customer's involvement in the service creation process through web tools, stimulating a closer relationship between the firm and its customers. The study develops into the following steps: we start from the objectives and the definition of the research question through the study of the literature; we try to find some assumptions that can be useful to analyze the selected case studies. Results help us to discuss the analysis and to get to some conclusions.
Keywords: 650; Open innovation; User innovation; Interactive marketing; Telecommunication sector